2010
DOI: 10.1029/2010gl045017
|View full text |Cite
|
Sign up to set email alerts
|

A simple MHD model for the formation of multiple dipolarization fronts

Abstract: A simplified MHD model is proposed that explains characteristic features of dipolarization fronts observed by the five‐probe THEMIS mission, and in particular the recurrent or multiple fronts, as structures arising from the nonlinear evolution of the interchange instability of the initial reconnection ejecta in the terrestrial magnetotail. Modeling the effects of the magnetic field curvature and plasma braking by an effective gravity and imposing an initial seed perturbation consistent with the observed dawn‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 27 publications
12
104
0
Order By: Relevance
“…To the contrary, in our model low entropy bubbles/dipolarization fronts are formed from the reconnection of the stretched geomagnetic field with the earthward moving flux ropes leading to the generation of reconnected flux tubes of increased volume V and low plasma density. The pressure balance inconsistency stems from the fact that the ratio β of particle pressure to magnetic pressure obtains unduly high values in the near-Earth equatorial plane when a flux tube shortens considerably as it convects earthward from −60 to −10 R E (Erickson and Wolf, 1980), assuming adiabatic compression of plasma during the earthward magnetoplasma transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the contrary, in our model low entropy bubbles/dipolarization fronts are formed from the reconnection of the stretched geomagnetic field with the earthward moving flux ropes leading to the generation of reconnected flux tubes of increased volume V and low plasma density. The pressure balance inconsistency stems from the fact that the ratio β of particle pressure to magnetic pressure obtains unduly high values in the near-Earth equatorial plane when a flux tube shortens considerably as it convects earthward from −60 to −10 R E (Erickson and Wolf, 1980), assuming adiabatic compression of plasma during the earthward magnetoplasma transport.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenological model introduced in this study provides a simple explanation of the so-called "pressure balance inconsistency" or "pressure crisis" problem first noted by Erickson and Wolf (1980), since it does not involve the arrival of flux tubes from the distant tail to the near-Earth region. To the contrary, in our model low entropy bubbles/dipolarization fronts are formed from the reconnection of the stretched geomagnetic field with the earthward moving flux ropes leading to the generation of reconnected flux tubes of increased volume V and low plasma density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations are that these recurrent appearances reflect multiple jet ejection or that they are due to the spacecraft's traversal of a highly structured front. Guzdar et al (2010) showed that the depolarization front could deform itself into a mushroom shape and proposed that the multiple sharp magnetic jumps seen in the time-series data were reproduced in a virtual observation along a cut through the mushroom-shaped front. 5 Magnetic field data from four THEMIS spacecraft aligned along the tail-axis observing a depolarization front sequentially at X = −20.1 R e , −16.7 R e and at −11.0 R e .…”
Section: Waves At Ion-scales and At Lower Frequenciesmentioning
confidence: 99%
“…Another example can be processes like Earthward and tailward depolarization front evolution connected to substorm events which are unstable to the interchange instability. Recent MHD numerical simulations of magnetotail current sheet and consequent depolarization front dynamics show different instability regimes (unsteady reconnection, kinking instability, interchange instability) leading to a final very turbulent state (Lapenta and Bettarini 2011a;Guzdar et al 2010) as reported in Fig. 11 displaying a two-dimensional clip of the density at the center of three-dimensional box.…”
Section: Discussionmentioning
confidence: 99%